Pemetaan Partisipatif Hutan Adat Desa Bayan - Webliana B, Kornelia; Prasetyo, Andrie Ridzki; Valentino, Niechi; Jemarut, Wihelmus; Juansyah, Raj'i Waldi; Hadi, M Rijalul Gozali1, Muhammad Anwar; Ariagunawan (Universitas Mataram, 2025)
The objective of this community service activity was to ascertain the location and extent of customary forests in Bayan Village, with the intention of subsequently preparing a map delineating the boundaries of these areas. The preparation of the map was conducted through a participatory approach, which involved the village government, customary leaders, representatives of indigenous communities, youth leaders, and communities situated in close proximity to the customary forest area. The location of the service was determined through the use of purposive sampling, with the following considerations taken into account: Bayan Village is notable for its extensive customary forest area, ranking among the largest in North Lombok Regency. However, there has been no data update related to the customary forest area since 2005. The data sources employed in this activity encompassed both secondary and primary data, which were subsequently classified into two distinct categories: primary data, comprising boundary digitization results, satellite imagery, village boundaries, village profiles, and pertinent literature; and secondary data, obtained from various sources, including satellite imagery, village boundaries, village profiles, and related literature. The data were analyzed using ArcGIS 10.8.2 software, resulting in a map visualization of the customary forest areas. The mapping results demonstrate that the Bayan Village Customary Forest is divided into four distinct areas: Bangket Bayan, Mandala, Pangempokan, and Tiu Rarangan. The total area of the customary forest in Bayan Village is 82.02 hectares, representing a decrease of 1.18 hectares from the 2005 mapping results, which recorded 83.2 hectares